2010
DOI: 10.1590/s0100-06832010000400037
|View full text |Cite
|
Sign up to set email alerts
|

Indicadores de qualidade de solos de área de mineração e metalurgia de chumbo: II - Mesofauna e plantas

Abstract: RESUMO A influência do manejo ou a adição de contaminante ao solo, normalmente, induz uma resposta mais rápida sobre a mesofauna do solo do que em outros atributos pedológicos, o que torna esses organismos bons indicadores de qualidade ambiental. Os objetivos deste trabalho foram identificar e quantificar os grupos de organismos da mesofauna dos solos e determinar os teores de Pb e Zn de plantas da área de mineração e metalurgia de Pb, no município de Adrianópolis (PR), de modo que fossem gerados indicadores b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 25 publications
0
9
0
6
Order By: Relevance
“…However, the seven months of soil management could have been adequate to investigate microbial changes in soil. Several authors have shown that the soil microbial community undergoes rapid changes in relation to environmental conditions (Faleiro & Andrade, 2011;Barros et al, 2010;Moreira & Siqueira, 2006). Furthermore, the AMF communities were most similar among samples from a similar geographical location (Figures 5 and 8).…”
Section: Figur Biofertigamentioning
confidence: 77%
See 1 more Smart Citation
“…However, the seven months of soil management could have been adequate to investigate microbial changes in soil. Several authors have shown that the soil microbial community undergoes rapid changes in relation to environmental conditions (Faleiro & Andrade, 2011;Barros et al, 2010;Moreira & Siqueira, 2006). Furthermore, the AMF communities were most similar among samples from a similar geographical location (Figures 5 and 8).…”
Section: Figur Biofertigamentioning
confidence: 77%
“…These changes may be due to the difference in the sample collection period and the soil humidification. Due to the sensitivity the environmental and anthropogenic interferences, the NFB and AMF communities and the soil microbial activity are good indicators to soil quality (Barros et al, 2010).…”
Section: Characterization Of Microbial Diversity By Dgge Profilementioning
confidence: 99%
“…The orders Acari and Collembola are the major constituents of soil mesofauna (Seastedt, 1984;Franklin et al, 2005;Yi et al, 2006;Barros et al, 2010), likely due to their high adaptive capacity (Yi et al, 2006), which is reflected in their feeding habits. According to Seastedt (1984), most Acari and Collembola species have mouthparts that can break down organic matter while they feed on the microflora (especially fungi) attached to it.…”
Section: Resultsmentioning
confidence: 99%
“…Although mining activity in the region ceased in the mid-1990s, close to 177,000 tons of Pb mining residues (tailings, slags) were left close to the company's facilities (Piedade et al, 2014) and are still deposited on the riverbanks. They are therefore an important source of contamination due to weathering processes, floods carriage, drag by rainfall, and percolation through the groundwater, among others (Andrade et al, 2009;Barros et al, 2010;Cotta et al, 2006;Gonçalves and Carvalho, 2006;Kummer et al, 2011;Piedade et al, 2014). Abessa et al (2014) compiled the information on the composition of the mining residues affecting RIR contamination levels and reported that both the tailings from local mines and the slags from the Plumbum plant included Pb, Cu, Cr, Zn and Ba, among other elements.…”
Section: Tier 0stressor Identificationmentioning
confidence: 99%